Analyzing motion characteristics and metabolic power of elite male handball players - Bassek, M.; Raabe, R.; Memmert, D.; Rein, R. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: In complex team sports like handball, analysis of player load (PL) during competition is a challenging task. However, correctly assessing load and physiological requirements underlying successful game performance is critical for efficient training regimes, optimizing performance, and preventing injuries. Recent work analyzed PL using position data of official team handball matches using time on court and distances covered in different velocity zones (1). However, these measures give little insight intro PL because of players frequent accelerations and decelerations. In contrast, estimating Metabolic Power (MP; 2) allows to capture the energy expenditure over time, including the cost of accelerations and decelerations. The present study therefore analyzed PL in elite male handball players using distance covered and MP.